Batteries: CuS Microspheres with Tunable Interlayer Space and Micropore as a High‐Rate and Long‐Life Anode for Sodium‐Ion Batteries (Adv. Energy Mater. 22/2018). Issue 22 (6th August 2018) - Xiao, Yuanhua; Su, Dangcheng; Wang, Xuezhao; Wu, Shide; Zhou, Liming; Shi, Ying; Fang, Shaoming; Cheng, Hui‐Ming; Li, Feng
Abstract : In article number1800930, Shaoming Fang, Feng Li, and co‐workers construct layered CuS microspheres with tunable interlayer space and pore volume, through a cost‐effective interaction method with the surfactant, cetyltrimethyl ammonium bromide (CTAB). As an anode material for sodium ion batteries, CuS‐CTAB microspheres reveal a high reversible capacity, excellent high‐rate performance, and long‐term cyclic stability.